TRADISI GONGCIK DI DESA PASUCEN TRANGKIL PATI GONGCIK TRADITION IN PASUCEN TRANGKIL VILLAGE - Sharita Ramadhanti; Nur Faizatur Rofiqoh; Yusuf Falaq (Universitas Baturaja, 2024)
The purpose of this research is to find out the meaning and history of the Gongcik tradition in Pasucen Village, Trangkil, Pati. The results showed that this tradition has existed since the Dutch colonial era but in its preservation Gongcik only survived in certain villages, one of which is Pasucen Village, Trangkil District, Pati Regency. Gongcik is a martial art wrapped in gamelan music with a combination of movements that become a dance, this tradition is usually performed in the event of earth alms, suronan, and so on. The Gongcik tradition needs to be preserved because it is rarely found.